Evaluation of Dynamic Pressure on Compound Perforated Wave Screen under Regular Waves - Naval Azam; Farzin Salmasi; Mohammad Ali Lotfollahi Yaghin; Javad Parsa; Ali Reza Mojtahedi (علوم و مهندسی آبیاری, 2018)
Coasts play an important role in economy of each country for their strategic location for residential, recreational, and industrial activities. Hence, a need has arisen to protect and maintain these coasts against waves and currents. (Rageh et al., 2009). The main cause of damage to coastal structures is the wave impact force. Protective structures such as submerged breakwaters, screen breakwaters, and various piles are often designed to provide additional attenuation of the impact force impact. The use of vertical slotted barriers can be a cost effective solution for wave energy dissipation when sloped rubble structures are not desirable. For a cost-effective design of such barriers, an accurate estimation of dynamic pressures characteristics is needed. Many experimental and theoretical studies were carried out for determining the dynamic pressures acting on different shapes or structures supported on piles. Neelamani & Sandhya (2005) investigated wave reflections, run-up and run-down, and wave pressures on plane, dentate and serrated seawalls. Krishnakumar et al. (2010) studied the effect of wave screens on the reduction of pressures and forces on a vertical wall on its lee side due to directional waves. Shih (2016) investigated the performance of a pervious pipe screen breakwater installed in front of a seawall in terms of reducing the wave impact force and wave pressure. The preceding brief review suggests that there is not much experimental data published on the wave induced dynamic pressures acting on compound wave screen. In this study, experimental investigations on wave pressures on different compound wave screen conﬁgurations were carried out in regular wave. The wave screen consists of a perforated wall that extends from above the seawater to above the seabed. The gap between pipes allows the seawaterexchange, the sediment transport and the ﬁsh passage and the results of this study can be used for a better hydrodynamic design of vertical structures.